Antioxidant Study of Three Curcuma Species and Screening of Antioxidant Components Using Stepwise Regression Analysis - Hu, Shu-Ping; Zhang, Yuan; Xiang, Zheng (Asian Journal of Chemistry, 2014)
This study evaluated the effectiveness of the antioxidant properties of fresh and dry rhizomes of Curcuma phaeocaulis, C. kwangsiensis and C. wenyujin based on their 1,1-diphenyl-2-picrylhydrazyl and hydroxyl radical scavenging activities, ferrous ion chelating ability and reducing power. Stepwise regression analysis was used to establish the component-effect relationship between HPLC profiling and half-maximal effective concentrations. The results demonstrated that 95 % ethanol and ethyl acetate extracts from the three Curcuma species at lower concentrations have higher DPPH and OH free radical scavenging rates. The leave-one-out cross-validation coefficients of the component-effect model of DPPH, OH and reduction methods were greater than 0.8, indicating that the component-effect model is highly robust and predictive. This study suggests that 95 % ethanol and ethyl acetate extracts from three Curcumas are rich sources of antioxidant substances and that multivariate regression analysis can be a useful tool for screening antioxidant components.